Early surgical treatment of postinfarction ventricular septal rupture - V. S. Moroz; N. D. Oryshchyn; S. S. Pavlyk; O. Y. Kushta; V. A. Tytyuk; Z. Z. Kurtyak (Ukrainian Journal of Cardiovascular Surgery, 2017)
Ventricular septal rupture (VSR) is the cause of up to 5% of deaths in the early period of myocardial infarction (MI). Surgical treatment of postinfarction VSR in the early period of MI is combined with a high risk, but can reduce the mortality rate of patients.Objective. To analyze the course of postinfarction VSR nd effectiveness of surgical treatment during the acute period of MI.Materials and methods. We performed surgical ventricular septal plasty for postinfarction VSR in acute period of MI in 5 patients of Lviv Regional Center of Cardiology. The diagnosis is established by echocardiography. Infarction exclusion technique (David) was used for the plasty. The time from the beginning to the IM to operations was from 1 to 5 days. One patient died of multiple organ failure, the other four have recovered, the follow-up is 11 to 36 months. In three patients we found residual shunt on the edge of the patch on the 1–2 day after operation, but it did not require reoperation.Conclusions. Ventricular septal plasty in acute period of MI has positive results. Echocardiography is a diagnostic method for postinfarction VSR and for residual shunting.